1982
DOI: 10.1002/j.1537-2197.1982.tb13248.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Mistletoe Pollen. V. Madagascan and Continental African Viscum L. (Viscaceae)

Abstract: Pollen characters of Madagascan and continental African Viscum are described and compared to those in Asia and Australia. The subprolate, tricolporate, nonuniformly sculptured pollen of Madagascan taxa is most similar to that of Asian species. Ultrastructurally, however, the completely granular equatorial ektexine of Madagascan Viscum is most similar to that of continental African taxa. Continental African Viscum, in contrast to Madagascan and Asian species, display a wide variation in pollen shape and apertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The outstanding work on the pollen morphology of extant Loranthaceae by Feuer & Kuijt (1979 , 1980 , 1985 ) and other Santalales lineages ( Maguire, Wurdack & Huang, 1974 ; Feuer, 1977 , 1978 , 1981 ; Feuer & Kuijt, 1978 , 1982 ; Feuer, Kuijt & Wiens, 1982 ) demonstrated that most pollen produced by members of the Loranthaceae cannot be confused with pollen from other angiosperm families ( Grímsson, Grimm & Zetter, 2017 ). Grímsson, Grimm & Zetter (2017) distinguished four general types (Pollen Type A, B, C, D), of which only one (Pollen Type A) could be confused with pollen of other Santalales lineages, and would unlikely be recognised as Loranthaceae pollen if found in a fossil pollen sample.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding work on the pollen morphology of extant Loranthaceae by Feuer & Kuijt (1979 , 1980 , 1985 ) and other Santalales lineages ( Maguire, Wurdack & Huang, 1974 ; Feuer, 1977 , 1978 , 1981 ; Feuer & Kuijt, 1978 , 1982 ; Feuer, Kuijt & Wiens, 1982 ) demonstrated that most pollen produced by members of the Loranthaceae cannot be confused with pollen from other angiosperm families ( Grímsson, Grimm & Zetter, 2017 ). Grímsson, Grimm & Zetter (2017) distinguished four general types (Pollen Type A, B, C, D), of which only one (Pollen Type A) could be confused with pollen of other Santalales lineages, and would unlikely be recognised as Loranthaceae pollen if found in a fossil pollen sample.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 contains the species discussed in this review, including the common names, the antioxidant studies, and the related references. It is evident that so far, the studies were influenced by the prevalent presence of European mistletoe and its utilization in complementary treatments in oncology [ 120 , 121 , 122 ], though there is an abundance of research focused on antioxidant activities. Southern African countries are a potential source of native, undiscovered, exceptional species [ 123 ].…”
Section: Discussionmentioning
confidence: 99%